Gendered innovations: harnessing the creative power of sex and gender analysis to discover new ideas and develop new technologies - Londa Schiebinger (Triple Helix, 2014)
"Gendered Innovations" integrate sex and gender analysis into all phases of basic and applied research to stimulate new knowledge and technologies. In so doing, Gendered Innovations enhance creativity, innovation, and gender equality. This paper reports on the interdisciplinary, international collaboration that produced: 1) 12 state-of-the-art methods of sex and gender analysis for science, health and medicine, engineering, and environmental research; and 2) and 25 case studies to illustrate how gender analysis leads to discovery. The project moves gender studies beyond identifying gender bias to prioritizing sex and gender analysis as resources to fuel new discoveries.
Keywords: 330; Assistive Technology; Gender Analysis; Gender Equality; Machine Translation; Standpoint Theory